La bibliothèque de Robert de Cotte - Geoffroy, Pierre (Abaton. Revista de figuración, representación e imágenes de la arquitectura, 2023)
The name Robert de Cotte is by now so familiar to any connoisseur of modern architecture that one wonders if there is anything left to discover. But despite the studies of his work, one aspect that has been little studied is his life, his family and his fortune. Thanks to the recent discovery of the inventory after the death of his wife, Catherine Bo-din, it is possible to shed more light on these different aspects. His library reflects the inspirations and interests of Robert de Cotte and bears witness to the taste and inspirations of an era and the culture of an enlightened person.